Investigation about the characterization of machine tool spindle stiffness for intelligent CNC end milling. (August 2015) - Sarhan, Ahmed A.D.; Matsubara, Atsushi
Abstract: This paper describes how to investigate the characterization of the machine tool spindle stiffness in radial direction for precise monitoring of cutting forces in end milling process by using displacement sensors. Four sensitive eddy-current displacement sensors are installed on the spindle housing of a machining center so that they can detect the radial motion of the rotating spindle. Thermocouples are also attached to the spindle structure, and the stability of the displacement sensing is examined. The change in spindle stiffness due to the spindle temperature and the speed is investigated. Finally, monitoring results of small and medium scale cutting forces in end milling operations are shown as a case study. Highlights: Spindle equipped with displacement and thermal sensors. The behavior of spindle displacement is investigated using displacement sensors. Spindle stiffness is investigated at different spindle speeds and temperatures. Tests for the monitoring of cutting forces in end milling operations are carried out.